Propuesta de diseño de una red convergente para optimizar el ancho de banda en la Institución Educativa Jean Piaget, año 2021 - Flores Torres, Joy Fredson (2023)
In the following research project, it is projective of a quantitative type and at a descriptive level and the research design is Solution Design, in which the design of a convergent network is proposed, in which voice, data and video are integrated. , so that the Jean Piaget educational institution can have a document that gives guidelines to be able to implement said network, if implemented, they will be able to run tools on the network that support the improvement of the teaching-learning process of students, it is also necessary take into account the bandwidth to be contracted, because in the city of Iquitos it is too expensive to be able to count on it, which is why the following is a general problem: To what extent does the design proposal for a convergent network will allow us to optimize the bandwidth at the Jean Piaget Educational Institution, year 2021”?, for which we have the following general objective: “Propose the Design of a convergent network to optimize the bandwidth at the Jean Piaget Educational Institution (IE) , year 2021", for which the results we have, as a result of what has been researched and developed, is that the Bandwidth (AB) to be contracted will be 13.23 MB, with which we confirm the General Hypothesis: "The Design proposal of a Converged network will allow for communication services at the IE Jean Piaget, 2021”.